LEGAL STUDY CONCERNING PROVISION ON THE DEVELOPMENT OF ENVIRONMENTAL FUNDS IN DEVELOPMENT OF PUBLIC FACILITIES AND INFRASTRUCTURE IN THE DEVELOPMENT OF BUILDING STORAGE OF EVIDENCE GOODS AND HOUSEHOLD RESISTANCE OF NORTH SUMATRA AREA - Junaedi Junaedi (Res Nullius Law Journal, 2020)
BUMN as a red template institution has long carried out a program that has similarities with the vision and mission of CSR which is a translation of the TJSL even though there were no regulations that obliged SOEs to do so. Potential donations to the public through PKBL are expected to provide greater benefits than those carried out by non-SOE corporations. Through the PKBL it is hoped that there will be an increase in the contribution of SOEs to the empowerment of the potential and condition of a synergic economic, social and environmental community so as to create equitable development. Besides having the main function of looking for profit, BUMN also has the duty to pay attention to social issues. In Article 88 paragraph (1) of Law No: 19 of 2003 concerning SOEs it is stated "SOEs can set aside a portion of their net income for the purposes of fostering small businesses / cooperatives and fostering communities around SOEs". But on the other hand, SOE is a form of PT which also has environmental social responsibility (TJSL) or often referred to as CSR, it is specifically regulated in article 74 paragraph (1) of Law No: 40 of 2007 concerning PT, "that the company those who carry out their business in and related to natural resources, are required to carry out corporate social and environmental responsibility activities." The purpose and objectives, based on the background of making this study is the purpose of the preparation of this study is to examine whether the effectiveness of BL assistance programs for the development of public facilities and infrastructure in the form of evidence storage buildings and detention centers of North Sumatra Regional Police. The problem in this paper is whether the grounds or reasons behind PTPN IV provide BL program assistance in the development of public facilities and infrastructure in the form of evidence storage buildings and detention centers of the North Sumatra Regional Police